OP0074 First Report of Circulating Micrornas in Tumour Necrosis Factor Receptor-Associated Periodic Syndrome (TRAPS). (23rd January 2014) - Galeazzi, M.; Obici, L.; Ferracin, M.; Fulci, V.; McDermott, M. F.; Lucherini, O. M.; Merlini, G.; Dickie, L.; Muscari, I.; Frediani, B.; Negrini, M.; Cimaz, R.; et al.
Abstract : Background: Tumor necrosis factor-receptor associated periodic syndrome (TRAPS) is the most common autosomal dominant autoinflammatory disorder. To the best of our knowledge circulating miRNAs in TRAPS, as well as in other monogenic autoinflammatory disorders have never been investigated. Objectives: to evaluate circulating microRNAs (miRNAs) levels in patients with TRAPS, in comparison to healthy controls, and to correlate their levels to parameters of disease activity and/or disease severity Methods: expression levels of circulating miRNAs were measured by Agilent microarrays in 29 serum samples from 15 TRAPS patients carrying mutations known to be associated with high disease penetrance and 8 healthy controls. Differentially expressed and clinically relevant miRNAs were detected using GeneSpring GX software Results: we identified a 6 miRNAs signature able to discriminate TRAPS from healthy controls. Moreover, 4 miRNAs were differentially expressed between patients treated with the interleukyn (IL)-1 receptor antagonist anakinra and untreated patients. Of them, miR-92a-3p expression was found to be reduced in untreated patients, while its expression levels were similar to healthy controls in those samples from patients during anakinra treatment. MiR-92b levels were inversely correlated with the number of fever attacks/year during the 1 st year from the index attack of TRAPS, while miR-377-5p levels were positively correlated with serum amyloid A (SAA) circulating levels. Conclusions: serum miRNAs levels show a baseline pattern in TRAPS, and may serve as potential markers of response to therapeutic intervention Disclosure of Interest: None Declared